IMPLEMENTING 5S SYSTEM IN PERSIA NOOR FACTORY, SHIRAZ, IRAN - Hojjati, Seyed Mohammad Hossein (International Journal of Industrial Engineering: Theory, Applications and Practice, 2011)
Among the eighteen members of Asian Productivity Organization, Iran is the seventeenth. The reason is the lack of properly usage of the great resources present in this country. 5s method is a methodology as basement for better usage of the resources in an organization, it is used to establish and maintain a quality environment that help in reducing waste and maintain a high degree of cleanliness and orderliness in the work place. This paper shows how 5s technique is used in Persia noor of Shiraz factory in Iran. Decisions which are made, actions which are done, and the results which are gained, Are presented in this paper.